PENDAMPINGAN MUTU PEMBELAJARAN ANAK USIA DINI DI RA AL FADILAH CIKEUSIK KABUPATEN PANDEGLANG BANTEN - Ende, Ende; Ruiyat, Suci Aprilyati (MAJU : Indonesian Journal of Community Empowerment, 2024)
Early childhood education aims to shape children's character, skills and basic knowledge. RA Al Fadilah Cikeusik in Pandeglang Regency is committed to providing a mentoring programme to improve the quality of learning. Six teachers participated in this mentoring programme. The programme aims to ensure that all children receive a high-quality education that supports their best development. Learning quality mentoring in RA Al Fadilah is carried out through several stages, namely Initial training, Direct Guidance, Evaluation. Mentoring in RA Al Fadilah shows significant results in improving early childhood learning. Improvements in teacher understanding, application of teaching methods, use of teaching media, quality of interaction, lesson planning, and parent participation are all evidence that the programme has successfully achieved its goals. Therefore, the programme can be used as a model to improve early childhood education elsewhere.